2011
DOI: 10.1002/jssc.201100152
|View full text |Cite
|
Sign up to set email alerts
|

Determination of bisphenol‐A levels in human amniotic fluid samples by liquid chromatography coupled with mass spectrometry

Abstract: Bisphenol A (BPA) is one of the environmental endocrine-disrupting chemicals used widely in common consumer products. There is an increasing concern about human exposure to BPA, particularly in fetuses, due to the potential adverse effects related to the estrogenic activity of BPA. In assessing environmental exposure to BPA, it is essential to have a sensitive, accurate and specific analytical method, particularly for low BPA levels in complex sample matrices. In this study, we developed and validated an accur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 26 publications
0
13
0
Order By: Relevance
“…We previously reported [25] a validated off-line SPE/LC-MS method for quantifying BPA levels in human aminiotic fluid. Based on this method, we further optimized the SPE procedures under different pHs of loading sample, wash steps, and elution solvents.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We previously reported [25] a validated off-line SPE/LC-MS method for quantifying BPA levels in human aminiotic fluid. Based on this method, we further optimized the SPE procedures under different pHs of loading sample, wash steps, and elution solvents.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, no mobile phase additives, such as formic acid, acetic acid, ammonium acetate or ammonia were added in our previous method [25] because we also found that they can cause severe signal suppression for BPA analysis. However, these methods could not be applied to analyze phthalate metabolites under the same analytical conditions since without organic acid (such as acetic acid) added in the mobile phase, the phthalate monoesters, especially MMP, MEP, MBP and MBzP, wouldn’t bind effectively to the stationary phase of the analytical column and eluted out in 2 mins.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all amniotic fluid has its origins in maternal plasma, which transports nutrients, electrolytes and water to the embryo, as well as any toxicants and xenobiotics that may be present in maternal circulation and are able to diffuse across the placenta. Not surprisingly, “waterborne” exposures to environmental factors occur; the presence of xenobiotics (9, 10), industrial pollutants (11, 12), medications (13), chemicals in household items (14, 15) and chemicals derived from lifestyle habits (16),(17) have been isolated from human amniotic fluid, which is swallowed, breathed in and recycled by the developing fetus beginning at about week 10 and continuing throughout gestation (8). Consequently, the absorption routes during embryogenesis in humans are probably similar to those in zebrafish, including dermal, gastrointestinal and respiratory, although this has not been rigorously tested.…”
Section: Zebrafish and Human Embryos: Living In A Fishbowlmentioning
confidence: 99%